Prediction of plasma efavirenz concentrations among HIV-positive patients taking efavirenz-containing combination antiretroviral therapy. Issue 1 (December 2017) - Huang, Sung-Hsi; Lin, Shu-Wen; Chang, Sui-Yuan; Lin, Ya-Ting; Chiang, Chieh; Hsiao, Chin-Fu; Sun, Hsin-Yun; Liu, Wen-Chun; Su, Yi-Ching; Hung, Chien-Ching; Chang, Shan-Chwen
Abstract We investigated the predictors of plasma mid-dose concentrations (C12) of efavirenz by enrolling 456 HIV-positive patients who had received 2 nucleos(t)ide reverse-transcriptase inhibitors plus efavirenz (600 mg daily) for 2 weeks or longer and had their CYP2B6 516G>T polymorphism and efavirenz C12 determined. The median efavirenz C12 was 2.41 mg/L (IQR, 1.93–3.14). In analysis of covariance models, patients with CYP2B6 516GT and TT genotypes compared to those with GG genotype had higher efavirenz C12 (for GT genotype, an increase by 0.976 mg/L [95%CI, 0.765–1.188], and TT genotype, 4.871 mg/L [95%CI, 4.126–5.616]), while per 10-kg increment in weight decreased C12 by 0.199 mg/L (95%CI, 0.111–0.287). Models incorporating CYP2B6 516G>T polymorphism and weight had moderate predictive values in predicting efavirenz C12 ≥ 2 mg/L (ROC area under curve = 0.706 [95%CI, 0.656–0.756]). In the absence of CYP2B6 516G>T polymorphism, weight ≤58 kg provided better predictabilities for efavirenz C12 ≥ 2 mg/L (probability, 77.1% [95%CI, 69.0–83.5%] for weight = 50 kg and 70.6% [95%CI, 64.1–76.4%] for weight = 58 kg).